Developing Kiratu Pocket Dictionary as Supplementary Media for Deaf Children - Wijaya, Muhammad Cahya Panca; Ma'arif, Iin Baroroh; Agustina, Ulfa Wulan; Afidah, Nurul (JoEMS (Journal of Education and Management Studies), 2024)
This research aimed to design the Dictionary as a Supplementary media named KIRATU for deaf children that could help them learn the English language. This dictionary application was focused on supplementary vocabulary. The research method of this research was the Research and Development method (R&D) that adopted the ADDIE model that consisted of five procedures, they were: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. This research involved seven deaf children of Sekolah Luar Biasa Negeri(SLBN) Jombang in senior high school. From those steps, the researcher got the result of the research. 1) The result of material validation was 93, 65% (Very Good category), 2) The result of media validation was 86% (very good category), and 3) The result of deaf experts validation was 91, 8% (very good category). Based on the result, the researcher concludes that the KIRATU application should be used for deaf children to add vocabulary.